2061 : odyssey three - Clarke, Arthur C. (Arthur Charles), 1917-2008. (New York : Ballantine Books, 1988)
Heywood Floyd, survivor of two previous encounters with the mysterious monoliths, must once again confront Dave Bowman, a newly independent HAL, and the power of an alien race.
"A Del Rey book.".
Library Journal.
Young Ad.-Adult.
Young Adult
Keywords: Science fiction